2018
DOI: 10.2147/ceor.s164747
|View full text |Cite
|
Sign up to set email alerts
|

Procedure costs associated with the use of Harmonic devices compared to conventional techniques in various surgeries: a systematic review and meta-analysis

Abstract: BackgroundAs compared to conventional techniques, recent meta-analyses have reported cost savings with Harmonic devices; however, only in thyroidectomy. Thus, the aim of this study was to evaluate the costs associated with Harmonic devices versus conventional techniques across a range of surgical procedures.MethodsA systematic search of MEDLINE, EMBASE, and Cochrane Library was conducted from inception to October 01, 2016 without language restrictions to identify randomized controlled trials comparing Harmonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
3
9
0
Order By: Relevance
“…23,38 One of the disadvantages of the use of Harmonic FOCUS® is the high expense of the device but it can be reused, furtherly this should be weighed with the reduction of the operative time, operating team time, operating room occupancy with more surgeries can be performed in the same operative session with better utilization of health resources and reduction of the waiting list, reduction of the anesthesia costs, pain medication, nursing time, morbidity treatment, redo surgeries, hospital stay, and eliminates the cost of sutures, accordingly decreasing the overall hospital costs which are evident with the use of Harmonic FOCUS®. 8,12,39,40 In our study the Harmonic FOCUS® group had significantly shorter hospital stay, p=0.002, which was due to the reduction in overall complications in this group, a similar result to that got by others. 8,14 The pitfall of a shortened length of hospital stay in the HS group was that there was a possibility of overlooking cases of symptomatic hypocalcaemia which may develop within 48 hours postthyroidectomy.…”
Section: Discussionsupporting
confidence: 87%
“…23,38 One of the disadvantages of the use of Harmonic FOCUS® is the high expense of the device but it can be reused, furtherly this should be weighed with the reduction of the operative time, operating team time, operating room occupancy with more surgeries can be performed in the same operative session with better utilization of health resources and reduction of the waiting list, reduction of the anesthesia costs, pain medication, nursing time, morbidity treatment, redo surgeries, hospital stay, and eliminates the cost of sutures, accordingly decreasing the overall hospital costs which are evident with the use of Harmonic FOCUS®. 8,12,39,40 In our study the Harmonic FOCUS® group had significantly shorter hospital stay, p=0.002, which was due to the reduction in overall complications in this group, a similar result to that got by others. 8,14 The pitfall of a shortened length of hospital stay in the HS group was that there was a possibility of overlooking cases of symptomatic hypocalcaemia which may develop within 48 hours postthyroidectomy.…”
Section: Discussionsupporting
confidence: 87%
“…This appears to be the first published study to assess the hospital budget impact of adopting an entire category of devices in the electrosurgical space. Moreover, this study used differences in resource use outcomes to model economic impact, demonstrating that improved hospital outcomes can lead to lower hospital costs, as is consistent with other literature 18,55,56 . Further, this category-wide approach may be more informative than traditional line-by-line item comparisons.…”
Section: Discussionsupporting
confidence: 78%
“…Ultrasonic devices are a type of advanced energy device that convert electrical energy to mechanical vibration, allowing simultaneous hemostasis and tissue transection 2,18 . Advanced bipolar devices use radiofrequency energy to achieve coagulation and hemostasis, but require an additional mechanical integrated knife blade for tissue transection 2,5,7,[15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is crucial to educate the operation theater staff, improve preoperative planning, and employ efficient surgical methods to decrease the effect of operative time on surgical outcomes [23]. Furthermore, a systematic review and meta-analysis by Cheng H et al showed that a reduction in operative time can significantly reduce the overall costs of the surgical procedure [24]. Thus, both time-and cost-effectiveness are crucial for the clinician while making surgical decisions [20].…”
Section: Discussionmentioning
confidence: 99%